(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
In today’s world, the main subject of globalization are large transnational corporations (TNCs), which have a significant impact on the world economy development. The study of TNC investment processes plays an important role for economics. The purpose of the paper is to highlighte the current trends of TNCs international investment activities. In 2018, the value of cross-border mergers and acquisitions (M&A) increased by 18 % due to the large size of transactions, especially in the chemical industry and services. The cost of the announced greenfield projects increased by 41%, an increase mainly was in mining, processing and construction. Regarding the manufacturing sector, the net M&A sales at the global level remained close to the 2017 level. Deal making in the pharmaceutical industry declined for the third successive year. M&A sales have more than doubled in chemical industry. In services, net M&A sales increased by over one third. The article highlights that there must be a stable political situation and an effective system of business regulation that provide the investor, ie TNCs, a guarantee of rights and protection of interests for the successful operation of TNCs in the host country. High level of corruption and misuse of funds, the complexity of doing business, the unstable political and economic situation in the country are the factors that negatively affect on the investment activities of TNCs. One of the promising areas of TNC investment activity is fintech – the newest and fastest growing sector of the global economy. Advanced achievements of scientific and technological progress, financial innovations, achievements and advantages of information, digital, network and intellectual components are concentrated in fintech today. ASEAN TNCs often merge fintech-start-ups and initiate fintech-departments to expand services and integrate financial technology into traditional businesses. Thus, the Malaysian bank CIMB Group in 2017 established a separate fintech-division in order to find innovative banking solutions. The construction of a mobile banking platform in Vietnam and the Philippines, a mobile payment wallet developed with the participation of Chinese and Thai companies are the examples of such projects.